Mata Kuliah Bahasa Jepang dalam Memberikan Kemampuan Beradaptasi Peserta Internship ke Jepang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The internship program in Japan is one of the international collaborations that is highly sought after by Indonesian students to gain global work experience. However, language, cultural differences, and work ethics often become major obstacles in the adaptation process of internship participants. The Japanese language course plays a strategic role in equipping students to adapt optimally in the Japanese work environment. This study aims to analyze the contribution of the Japanese language course in enhancing the adaptation skills of internship participants in Japan, focusing on linguistic aspects, culture, intercultural communication, and professional readiness. The research method used is a literature review by examining 20 relevant academic articles sourced from national journals and trusted academic databases. The findings indicate that learning Japanese, integrated with an understanding of Japanese culture, work ethics, and professional context, improves students' readiness to face internship challenges. Courses such as Nihonjijo and Bijinesu Nihongo play a significant role in accelerating adaptation, reducing culture shock, and boosting students' confidence and work performance. Additionally, the internship program also contributes to the development of students' soft skills, such as discipline, responsibility, and adaptability.